Celebrity Authorship and Afterlives in English and American Literature - Franssen, Gaston; Honings, Rick.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book maps the history of literary celebrity from the early nineteenth century to the present, paying special attention to the authors' crafting of their writerly self as well as the afterlife of their public image. Case studies are John Keats, Edgar Allan Poe, Eliza Cook, Herman Melville, Oscar Wilde, Gertrude Stein, J.D. Salinger and Zadie Smith. Literary celebrity is part and parcel of modern literary culture, yet it continues to raise intriguing questions about the nature of authorship, writerly fame and the tension between authorial self-fashioning and public appropriation. This volume provides unique insights into the phenomenon.
Introduction; Gaston Franssen and Rick Honings -- 1. A Friendly Return of the Author: John Keats (1795-1821); Eric Eisner -- 2. Hero of Horror: Edgar Allan Poe (1809-1849); Evert Jan van Leeuwen -- 3. Victorian Iconoclast: Eliza Cook (1818-1889); Alexis Easley -- 4. The Daguerreotype Devil: Herman Melville (1819-1891); Kevin J. Hayes -- 5. The Art of Creating a Great Sensation: Oscar Wilde (1854-1900); Sandra Mayer -- 6. Production and Reproduction: Gertrude Stein (1874-1946); Rod Rosenquist -- 7. The Silence of the Celebrity: J.D. Salinger (1919-2010); Gaston Franssen -- 8. Public and Private Posture: Zadie Smith (1975); Odile Heynders -- Bibliography -- Index.-.
Keywords: British literature; America-Literatures.; Literature, Modern-20th century